Understanding the Kinetic Energy Deposition within Molecular Clouds - Yuan, Lixia; Yang, Ji; Du, Fujun; Su, Yang; Zhang, Shaobo; Yan, Qing-Zeng; Sun, Yan; Zhou, Xin; Chen, Xuepeng; Wang, Hongchi; Chen, Zhiwei (The Astrophysical journal, 2023)
According to the structures traced by 13 CO spectral lines within 12 CO molecular clouds (MCs), we investigate the contributions of their internal gas motions and relative motions to the total velocity dispersions of 12 CO MCs. Our samples of 2851 12 CO MCs harbor a total of 9556 individual 13 CO structures, among which 1848 MCs (∼65%) have one individual 13 CO structure and the other 1003 MCs (∼35%) have multiple 13 CO structures. We find that the contribution of the relative motion between 13 CO structures ( σ 13 CO , re ) is larger than that from their internal gas motion ( σ 13 CO , in ) in ∼62% of 1003 MCs in the “Multiple” regime. In addition, we find that σ 13 CO , re tends to increase with the total velocity dispersion ( σ 12 CO , tot ) in our samples, especially for MCs with multiple 13 CO structures. This result provides a manifestation of macroturbulence within MCs, which gradually becomes the dominant way of storing kinetic energy along with the development of MC scales.